ANALISIS PERAN DAN FUNGSI MUSYAWARAH DESA BERDASARKAN UU DESA NO 3 TAHUN 2024 DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA (STUDI KASUS: DESA SUKANDEBI KECAMATAN NAMAN TERAN KABUPATEN KARO) - Lase, Yesi Maria; Rajagukguk, Jonson; Tobing, Artha L (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study is entitled "Analysis of the Role and Function of Village Deliberations Based on Village Law No. 3 of 2024 in Increasing Community Participation in Village Development (Study in Sukandebi Village, Naman Teran District). The purpose of this study is to analyze the implementation of Village Deliberations (Musdes) in Sukandebi Village, examine their roles and functions as mandated by Village Law No. 3 of 2024, and assess the level of community participation in village development. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The research informants consisted of village officials and village residents. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The research results indicate that the Village Deliberation (Musyawarah Desa) in Sukandebi Village has been held routinely, as mandated by Village Law No. 3 of 2024. The Musdes serves as a forum for community participation, joint decision-making, and a means of developing the Village Work Plan (RKPDes). Musdes decisions influence the priority use of Village Funds, particularly for infrastructure development and community empowerment. However, community participation in the planning and monitoring stages remains limited due to the dominance of village elites, a lack of outreach, and low public legal awareness. Higher participation is seen in the implementation phase, such as mutual cooperation activities. The conclusion of this study is that the Village Deliberation (Musyawarah Desa) in Sukandebi Village has been implemented according to regulations, but is not yet fully inclusive and participatory. Therefore, increased outreach, transparency, and active involvement of various community elements (youth, women, and vulnerable groups) are needed to ensure the Musdes truly becomes a democratic village forum capable of realizing community-driven development.